Participatory market chain appraisal for the full range of agroforestry products including market trends and growing markets - Amatya, S. M.; Nuberg, I.; Cedamon, E.; Shrestha, K. K.; Pandit, B. H.; Aulia, P.; Joshi, M.; Dhakal, B. (Banko Janakari, 2018)
This paper focuses on the participatory market chain analysis of agroforestry products in six sites of two districts (Kavre and Lamjung) of Nepal. In total, 93 market actors were involved in the study, in which 80 persons were purposively selected from Local Resource Person (LRP) and Local Resource Group (LRG) members and 13 persons were randomly selected from the local, district and national level traders. Primary data on agroforestry products was collected through Participatory Rural Appraisal (PRA) tools following several field visits. Fourteen agroforestry products in Lamjung and 20 agroforestry products in Kavrepalanchok district were selected for analysis. The findings showed that small-scale production and insufficient service to farmers from the village level agriculture collection centers and cooperatives are the major constraints to effective and efficient market chain development and management. The main factors responsible for increasing the production of agroforestry products are the rise in awareness among LRPs/ LRGs about agroforestry practices along with institutional and policy development to facilitate the marketing of agroforestry products. The paper concludes by highlighting the controlling factors in agroforestry business. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, page: 32-45